(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the use of different substrates (coconut fiber and Carolina Soil®) and light spectra (black, dark blue, light blue, purple, pink, green, light yellow, yellow, orange and red) in the production of microgreens. The experimental design in the first experiment was completely randomized, in a 2x3 factorial scheme, resulting in six treatments with two levels for the substrate factor (coconut fiber and commercial substitute Carolina Soil®) and three levels for the cultivar factor (Rúcula Surya, Carrot Radesh ) and Shankar Beet). The experimental design of the second experiment was also completely randomized, in a one-factor scheme with 10 levels for the light spectrum factor (black, light blue, blue, purple, pink, green, yellow, dark yellow, orange and red). The first experiment was carried out with the length of the shoot (cm) and the mass of the shoot area and the shoot root (g). No second was tested for shoot and root length (cm) as well as shoot and root dry and fresh mass (g). In the first study, the analysis of variance of the commercial substrate Carolina Soil® stood out, with seedlings presenting shoot length of 4.94 cm. In the second experiment, the filter with purple light spectrum showed the best results for the cultivation of microgreen Arugula Surya with shoot length of 3.29 cm. It was concluded that the commercial substrate Carolina Soil® and the spectrum of purple light were more suitable for the cultivation of microgreens.